Antimicrobial and Antioxidant Activities of Black Cumin Seed (Nigella sativa) Ethanol Extract - Reni Yuslianti, Euis; Susanto, Agus; Sutjiatmo, Afifah Bambang; Widowati, Wahyu; Ayuni, Vini; Hadiprasetyo, Dhanar Septyawan (Bogor Agricultural University, Indonesia, 2025)
Oral health faces significant challenges due to increasing dental infections by pathogenic microbes such as Porphyromonas gingivalis, Streptococcus mutans, and Candida albicans. Topical antioxidants in toothpaste, gel, and mouthwash are often used to treat dental diseases. There is a growing interest in finding natural alternatives for oral hygiene without side effects compared to conventional toothpaste formulations. Nigella sativa (black cumin) has various pharmaceutical efficacy, making it a valuable plant-based source medicinal compound. This study evaluated black cumin ethanol extract's (BCSE) antimicrobial and antioxidant activities. Antibacterial effectiveness was evaluated through Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), and disc diffusion assays against P. gingivalis, S. mutans, and C. albicans. Antioxidant activity was reported based on DPPH scavenging, ABTS reduction, H2O2 scavenging, and NO scavenging assays. Black cumin seed ethanolic extract (BCSE) showed antibacterial activity of 4.49 mm, 4.33 mm, and 7.12 mm for P. gingivalis, S. mutans, and C. albicans, respectively, with zones of inhibition increasing in a concentration-dependent manner (p<0.05). MIC and MBC evaluations also revealed that MIC for S. mutans was achieved at 12.5% BCSE concentration, while P. gingivalis and C. albicans required 25%, and MBC reached 100%. The IC50 for DPPH, ABTS, NO, and H2O2 were 25.41, 69.93, 87.18, and 95.16 μg/ml, respectively. The antioxidant activity increased in a concentration-dependent manner, especially at 100 µg/ml of BCSE. Based on these results, BCSE could be an optional ingredient in toothpaste.